Ni–Fe nanoframes via a unique structural formation induced by sonochemical etching. Issue 90 (26th October 2022) - Alowasheeir, Azhar; Nara, Hiroki; Eguchi, Miharu; Yamauchi, Yusuke
Abstract : A Ni–Fe nanoframe exhibits unique structural merits including 3D open structure and high surface area, enhancing electrochemical properties for oxygen-evolution reaction (OER). Abstract : A uniform nanoframe structure derived from a Prussian blue analogue (PBA) with an internal cavity is successfully synthesized by sonochemical etching. The uniquely structured PBA nanoframes possess a three-dimensional open structure and high surface area, resulting in enhanced electrochemical properties for the oxygen evolution reaction as a model reaction.